PERAN PEMERINTAH DAERAH DALAM MEMELIHARA KETENTERAMAN DAN KETERTIBAN UMUM (STUDI PADA PENANGANAN PENYEBARAN VIRUS COVID 19 DI PROVINSI DKI JAKARTA) - Agung Nurrahman (Fakultas Hukum Tata Pemerintahan, 2020)
The focus of this study is to determine the role of the DKI Jakarta Provincial Government in maintaining peace and public order in dealing with the spread of Covid-19 in Indonesia. The method of writing articles is to use library research. The conclusions obtained are: the role of the DKI Jakarta Provincial Government in maintaining the peace of the people of DKI Jakarta in facing the spread of Covid-19 has been carried out quite well. This can be seen from the concrete efforts that have been made since January 2020. The concrete efforts are in the form of preventive measures, short-term direction to be followed up and anticipatory efforts in dealing with Covid-19 in the DKI Jakarta area. The suggestions that can be made include the following: 1) The Provincial Government of DKI Jakarta needs to improve coordination with the central government with regard to data transparency; 2) The Provincial Government of DKI Jakarta needs to increase the dissemination of actual and trusted information to the public widely with any media both print media, electronic media and social media; 3) The Provincial Government of DKI Jakarta needs to increase close supervision to the public so that they can comply with appeals related to the procedures for preventing the spread of Covid-19; 4) Further research / studies are needed in relation to the Jakarta people's happiness index when the spread of Covid-19 occurs in relation to the role of the DKI Jakarta Provincial Government in maintaining peace and public order.